Assessment of knowledge, attitude and practices among operating room staff nurses towards the standard and transmission-based precaution in University Hospital - Mohd Ali, Sharif (2009)
These precautions are strongly recommended as the guidelines for preventing infections and ensuring occupational safety. This survey discussed on the level of knowledge, attitude and practices among OR staff nurses mainly related to standard precaution and transmission·based precautions. The specific objective of this survey are to identify relationship between variable demographic profiles of participants towards these precautions and to characterize the relation between knowledge, attitude and practices towards standard precaution and 1ransmission-based precautions. This was a self-reported survey conducted during April2009. Seventy-five out of 100 operating room staff nurses had returned back the completed questionnaires on the same day the questions had been distributed. The questionnaires comprised of three major components; the knowledge, the attitudes and the practices, towards the standard and transmission- based precautions. There was significant differences towards the standard and transmission precautions were found among OR female staff nurses in term of practices as compared to OR male staff nurses. There were weak correlation on level of knowledge among younger age of female staff. However, the overall result did not showed any clear correlation and there was no significant differences in demographic profiles. This study broadly profiles knowledge, attitudes and pmctice patterns of operating room staff, which may benefit healthcare educators in planning and developing appropriate educational programmes, may help organizations to provide a safe workplace climate and may aid healthcare workers to learn the important of personal responsibility in preventing infectious disease transmission to patients, co-workers and even themselves.